2001
DOI: 10.1046/j.1525-1497.2001.016008567.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of patient letter reminders on cervical cancer screening

Abstract: OBJECTIVE:To perform a meta-analysis on existing randomized controlled trials to investigate the efficacy of patient letter reminders on increasing cervical cancer screening using Pap smears. METHODS:A search was conducted for all relevant published and unpublished studies between the years 1966 and 2000. Eligibility criteria included randomized controlled studies that examined populations due for Pap smear screening. The intervention studied was in the form of a reminder letter. The Mantel-Haenszel method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 18 publications
2
40
0
1
Order By: Relevance
“…The very small aggregate effect size is similar to effect sizes found from meta-analyses of patient letter reminders for cervical cancer screening (OR = 1.64; Tseng et al, 2001) and of tailored self-help materials promoting smoking cessation (OR = 1.42; Lancaster and Stead, 2006). The small size may be due to an increase in mammography rates in the general population (Legler, 2002).…”
Section: Discussionsupporting
confidence: 59%
“…The very small aggregate effect size is similar to effect sizes found from meta-analyses of patient letter reminders for cervical cancer screening (OR = 1.64; Tseng et al, 2001) and of tailored self-help materials promoting smoking cessation (OR = 1.42; Lancaster and Stead, 2006). The small size may be due to an increase in mammography rates in the general population (Legler, 2002).…”
Section: Discussionsupporting
confidence: 59%
“…Patient reminders have been shown to be effective in increasing breast and cervical cancer screening rates. [29][30][31][32] Reported NCQA recognition as a PCMH also was associated with increased use of comparative performance reports and automated reports to alert providers of patients due for cancer screening outside the context of the clinical visit. Theoretical and empirical evidence supports the efficacy of physician audits and feedback in improving cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] By contrast, electronic physician reminders have little effect on screening rates, and solitary, lower-cost interventions (mailed patient reminders, automated phone calls) increase screening rates, but only modestly. 6,[13][14][15][16][17] However, several low-cost interventions might be combined to improve effect sizes. Stone et al reviewed interventions to improve preventive healthcare services and showed an additive effect of combined interventions.…”
Section: Introductionmentioning
confidence: 99%